Haemopoietic System of the Anurans: the Role of Bone Marrow and Liver - Akulenko, N.M. (Вестник зоологии, 2012)
The haemopoietic activity of the frog, Pelophylax ridibundus was investigated during the year. Liver and bone marrow myelograms were examined in the different seasons using the special indexes and coefficients. It was shown the presence of the erythroid and granulocytic differentiation during the year in the both organs. In the bone marrow is changing the total number of the non-diferentiated haemopoietic cells, but ratio between erythroid and granulocytic progenitors is stabile. The haemopoietic activity of the liver has more prominent season variation in comparison with the marrow, but their total significance is comparable. The erythrocytic differentiation is more prominent during the summer and autumn, but granulocytic one took place in the spring and summer. Гемопоэтическую активность костного мозга и печени озерной лягушки (Pelophylax ridibundus) исследовали в течение года. С помощью специальных коэффициентов и показателей анализировались миелограммы костного мозга и печени, определенные в различные сезоны. Показано наличие в обоих органах дифференцировки эритроидного и миелоидного ростков в течение года. В костном мозге изменяется общее количество недифференцированных предшественников кроветворения, но соотношение эритроидных и гранулоцитарных предшественников остается стабильным. Гемопоэтическая активность печени имеет более выраженные сезонные колебания, хотя её общее значение для гемопоэза сравнимо с костным мозгом. Дифференцировка эритроцитов более выражена летом и осенью, а дифференцировка гранулоцитов — весной и летом.